STEM Education Policy in Maine and the Nation - Keller, Thomas (Maine Policy Review, 2012)
Thomas Keller provides an overview of K-12 STEM (science, technology, engineering, and math) education policy in Maine and the nation, and makes recommendations for several agencies in the state. He argues that although standards and assessment are important, there need to be corresponding changes instructional materials methods and in school culture. Although we do not yet have a fully integrated STEM curriculum, Keller suggests that “we are overdue for interdisciplinary work where possible.”